Pastoral power in the community pharmacy: a Foucauldian analysis of services to promote patient adherence to new medicine use - Waring, Justin; Latif, Asam; Boyd, Matthew; Barber, Nick; Elliott, Rachel (Elsevier, 2016)
Community pharmacists play a growing role in the delivery of primary healthcare. This has led manyto consider the changing power of the pharmacy profession in relation to other professions and patient groups. This paper contributes to these debates through developing a Foucauldian analysis of the changing dynamics of power brought about by extended roles in medicines management and patient education. Examining the New Medicine Service, the study considers how both patient and pharmacist subjectivities are transformed as pharmacists seek to survey patient’s medicine use, diagnose non-adherence to prescribed medicines, and provide education to promote behaviour change. These extended roles in medicines management and patient education expand the ‘pharmacy gaze’ to further aspects of patient health and lifestyle, and more significantly, established a form of ‘pastoral power’ as pharmacists become responsible for shaping patients’ self-regulating subjectivities. In concert, pharmacists are themselves enrolled within a new governing regime where their identities are conditioned by corporate and policy rationalities for the modernisation of primary care.